(3fbhd eNJdaIs ((3eMeO Hf ESeGYjd GdCejQ s)
(3ChdgG (B:s
(3dYHO Gddg Hf GdeHGQc GdNQSGfi QMeg Gddg hQVi Yfg (B:_ (3Gddg HOaY HGdSWGf eYVdI Yf OjffG QMeI efg hQVhGfG s
(3BNQgG (B:s
(3hEf eYGfi bUU GdChdjf eGRGOgG GdbQBf GdcQje MdGhg hWQGhg acCfgG cd Mjf JUOQ WQjI HSHH GdYHGQGJ GdbQBfjI ceG eQQfG hPcQfG GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HghGeTgG JYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs